2000
DOI: 10.1007/s001980050288
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Self-Report of Fractures: Results from a Prospective Study in Men and Women Across Europe

Abstract: In population-based studies of osteoporosis, ascertainment of fractures is typically based on self-report, with subsequent verification by medical records. The aim of this analysis was to assess the validity of self-report of incident nonspine fractures using a postal questionnaire. The degree of overreporting of fracture (false positives) was assessed by comparing self-reports of new fracture from respondents in the multicenter European Prospective Osteoporosis Study with data from other sources including rad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
125
3
1

Year Published

2001
2001
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 179 publications
(134 citation statements)
references
References 10 publications
(16 reference statements)
5
125
3
1
Order By: Relevance
“…Under-and overreporting can occur owing to poor recall. (44) However, our fracture incidence corresponds to published data, (2) and the accuracy for self-report of fractures was found to be good in postmenopausal women for forearm or hip fractures. (45) Moreover, imprecise data would be expected to weaken the observed associations and in general underestimate associations.…”
Section: Discussionsupporting
confidence: 86%
“…Under-and overreporting can occur owing to poor recall. (44) However, our fracture incidence corresponds to published data, (2) and the accuracy for self-report of fractures was found to be good in postmenopausal women for forearm or hip fractures. (45) Moreover, imprecise data would be expected to weaken the observed associations and in general underestimate associations.…”
Section: Discussionsupporting
confidence: 86%
“…It should be noted that self-reported vertebral fractures are likely to be symptomatic; thus, the results of our study cannot be applied to asymptomatic vertebral fractures. Although a number of studies have shown the selfreporting of limb fractures to be accurate [4][5][6][7], we were unable to demonstrate accurate reporting of upper limb or hip fractures, even for those occurring in the last 5 years. We further investigated nine false positive cases of upper limb fracture reported in the last 5 years and found that five were due to high-energy trauma, one was a fracture at a different anatomical site (the clavicle), one involved fractures predating the study period, and two cases did not involve fractures.…”
Section: Discussioncontrasting
confidence: 77%
“…Several validation studies have confirmed self-reported non-vertebral fractures in Caucasian populations [4][5][6][7]; however, very few studies have addressed the accuracy of selfreported vertebral fractures. One reason may be that vertebral fractures are not common in such populations.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of VFs in acromegalic patients largely exceeded the prevalence in the control population, in all age groups (25). In addition, large European population-based cohort studies also report a much lower prevalence of VFs in both men and women (28)(29)(30)(31)(32), comparable to the findings in the Dutch reference cohort. Our findings, based on the scoring of two independent scorers and confirmed by an experienced radiologist, demonstrate that the prevalence of VFs in acromegalic women, but even more so in acromegalic men, exceeds the reported prevalence of VFs in the general population, including the Dutch population.…”
Section: Discussionmentioning
confidence: 52%